2012
DOI: 10.1097/meg.0b013e32834dfdfa
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal gangliocytic paraganglioma with lymph node metastasis and an 8-year follow-up

Abstract: Gangliocytic paraganglioma (GP) is a rare tumor, usually located in the second part of the duodenum. On pathological examination, GP is characterized by the association of the histological features of paragangliomas, ganglioneuromas, and carcinoid tumors. Classical clinical presentations are upper gastrointestinal bleeding and abdominal pain. Preoperative diagnosis is difficult because of the submucosal site of the tumor, with usually negative mucosal biopsies. Endoscopic ultrasound helps establish the diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Hence, it has the features of a ganglioneuroma, a paraganglioma, and a carcinoid tumor. Gangliocytic paraganglioma has been known to arise from endodermal neuroectodermal complex [11]. Similarly, paraganglioma and carcinoid tumor seem to coexist by similar mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, it has the features of a ganglioneuroma, a paraganglioma, and a carcinoid tumor. Gangliocytic paraganglioma has been known to arise from endodermal neuroectodermal complex [11]. Similarly, paraganglioma and carcinoid tumor seem to coexist by similar mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…The vast majority of GPs is found in the duodenum (90.1%). However, GPs have also been reported at other sites along the gastrointestinal, respiratory and urogenital tracts, as well as in the scalp, vertebral column and mediastinum 4 5 11 13 14. Paragangliomas and phaeochromocytomas as a collective are attributed to hereditary and germline mutations in at least 30% of cases (mainly due to succinate dehydrogenase gene mutations), with 70% occurring sporadically.…”
Section: Discussionmentioning
confidence: 99%
“…Given their tendency to arise in the duodenum, GPs most commonly present as gastrointestinal bleeding, abdominal pain and anaemia. Biliary obstruction is considered extremely rare (4.6% of all reported GPs) 4 11. GPs are usually benign and non-functional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Previous GP treatment algorithms based on tumor size and lymph node status have proposed that endoscopic removal could be considered if the tumor is small (<2 cm) with no evidence of peritumoral lymph nodes on CT scan. 4 In terms of tumor size, we suggest that tumors larger than 2 cm can be treated with endoscopic resection. Previous reports have confirmed that endoscopic resection for GP larger than 2 cm can be performed without complication, 8,9 with the largest reported tumor measuring 4 cm in size.…”
Section: 박세정 등 십이지장 신경절세포 부신경절종의 내시경 절제mentioning
confidence: 99%